SEBARAN, POTENSI DAN KUALITAS KAYU EBONI (Diospyros celebica Bakh.) DI SULAWESI - Muhammad Asdar; T.A. Prayitno; Ganis Lukmandaru; Eny Faridah (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
Ebony (Diospyros celebica Bakh.) isan endemic species of Sulawesi. The heartwood of ebony is composed of a series of axial and alternating black and paler streaks. Thisstreak pattern determinesof wood quality. Excessive exploitation causes ebony become scarce and has been classified as vulnerable by IUCN and Appendix II by UNEP - WCMC. Currentdistribution, potency (standing stock) and wood quality of each natural habitat of ebony in Sulawesi are not yet known. This study aims to determine the distribution, potency and wood quality on its natural habitat in Sulawesi. Standing stock data obtained with inventory and the results of the previous inventory.  GPS coordinates of each habitat is taken to make a map. Streaks quality class based on ebony factory standard in Palu and Makassar. The results showed that habitat of ebony was naturally found in Districts of Gowa, Maros, Pangkep, Barru, Sidenreng Rappang, Luwu, Luwu Timur (South Sulawesi Province), Mamuju (West Sulawesi Province), Donggala, Parigi Moutong, Poso and Morowali (Central Sulawesi Province).  The highest standing stock was found at Cenrana, Maros which is about 95,05 m3ha-1.  Most of the remaining ebony habitat were found in the protected areas. Wood quality class A and B were found in Sausu and Poso while other areas classified as class C. Key Words:  Ebony Wood,  Endemic Species Of Sulawesi, Strike Quality